Content and technological aspects of the development and application of electronic educational resources in pedagogical disciplines for foreign students - Zakharova, Svetlana N. (University Pedagogical Journal, 2024)
The article presents the design experience and some aspects of the use of electronic educational resources developed on the basis of the Moodle system for foreign students in the specialty 706011302 «Philological education».
Keywords: higher education; foreign students; electronic educational resources